Knowledge and Truth in the Thought of Jizang (549–623) - Rogacz, Dawid (My University, 2016)
The aim of this paper is to examine Jizang’s theory of knowledge and truth in terms of contemporary philosophy. Firstly, I present the main areas of Madhyamaka thought, especially those concerning human knowledge and cognition, enunciated in Nagarjuna’s Vigrahavyāvartani. Secondly, I raise the issue of the acceptance of Madhyamaka in the area of Chinese thought, which provides us with the question of the inception and development of the sānlùn zōng – the Three Treatises School. Thirdly, I expound the main points and key notions of Jizang’s philosophy: the crucial concepts of the “refutation of erroneous views as the illumination of right views” (bóxiè xiànzhēn) and “the Four Levels of the Two Kinds of Truth” (sìzhŏng èrdí). I try to explicate and develop these ideas in terms of modern epistemology, which in the first instance is related to the Münschausen trilemma.
Keywords: Jizang; Sanlun; Three Treatises; Madhyamaka; Nagarjuna; Buddhist epistemology; theory of two truths; Chinese Buddhism; Münschausen trilemma